Record Slide Show PowerPoint sebagai Alternatif Media Pembelajaran Audio Visual pada Pascapandemi - Alatas, Mochamad Arifin; Albaburrahim, Albaburrahim (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research is motivated by the increasing need and lack of knowledge of making learning media during the pandemic. This study aims to describe the procedure for using PowerPoint slide show records as an alternative to audio-visual learning media in the post-pandemic. This research uses a descriptive qualitative research method. The method of data collection in this research is the documentation technique, namely documenting the procedure for using PowerPoint slide show records as an alternative to audio-visual learning media. The result of this research is that the procedure for using PowerPoint slide show records as an alternative to audio-visual learning media in the post-pandemic has several stages. These stages include 1) planning, 2) making, and 3) publication.